Polimorfisme Protein Darah Transferrin Domba Padjadjaran Jantan Dewasa di Kampung Nenggeng Kecamatan Darangdan Kabupaten Purwakarta Jawa Barat - Yuliana Kolo; Sri Bandiati Komar Prajoga; Dudi Dudi (Program Studi Peternakan, Fakultas Pertanian, Universitas Timor, 2022)
This study aim to determine frequency gene and transferrin protein heterozygosity of male Padjadjaran sheep. Blood sample taken were 46 male Padjadjaran sheep. The research method will be used in this study descriptive method, namely the ram will be used as a stud with laboratory analysis used is the SDS-PAGE (Sodium Dodecyl Sulfate-Polyacrylamide Gel Electrophoresis) method. SDS-PAGE was used detect the appearance of blood protein bands. The transferrin frequency gene was calculated by the general formula for population genetic. Heterozygosity of transferrin protein was observed to determine the equilibrium status of Hardy Weinberg's Law. The results showed that there were two transferrin allele, namely TfA and TfB. The frequency of TfA gene is greater than that of TfB. Transferrin heterozygosity indicates compliance with the Hardy-Weinberg law equilibrium.